Glomalin related soil protein, soil aggregate stability and soil aggregate-associated organic carbon under agroforestry practices in southern Ethiopia - Nebiyou Masebo; Emiru Birhane; Serekebrehane Takele; Araceli Perez-Sanz; Juan J. Lucena; Zerihun Belay; Agena Anjulo; Felipe Yunta (BMC Ecology and Evolution)
Abstract Land degradation in Ethiopia is escalating due to high population density and the shift from tree-based agricultural systems, like agroforestry practices (AFP), to monoculture farming. These land use changes, compounded by climate change, threaten biodiversity and soil resources. Key soil health parameters, such as glomalin, soil aggregation, and aggregate stability, are negatively impacted by such practices. Agroforestry is proposed as a sustainable alternative to address these challenges. This study aimed to evaluate the effects of AFPs on soil glomalin, soil aggregate stability (mean weight diameter, MWD), and the relationship between soil aggregates and soil organic carbon (SOC). Undisturbed soil samples were collected from 0 to 30 cm and 30–60 cm depths in four land use types: home garden (HAFP), cropland (ClAFP), woodlot (WlAFP), and trees on soil and water conservation-based agroforestry (TSWAFP). Results showed significantly higher glomalin-related soil protein (GRSP) in HAFP and WlAFP compared to ClAFP and TSWAFP (p < 0.05). HAFP also exhibited the highest soil aggregate stability (SAS) and MWD, followed by WlAFP. These findings suggest that agroforestry practices can significantly enhance soil health, ecosystem stability, and long-term sustainability, contributing to land restoration efforts.